Differential microlensing measurements of quasar broad-line kinematics in Q2237+0305 - O’Dowd, M.; Bate, N.; Webster, R.; Wayth, Randall; Labrie, K. (Wiley-Blackwell Publishing Ltd., 2011)
The detailed workings of the central engines of powerful quasars remain a mystery. This is primarily due to the fact that, at their cosmological distances, the inner regions of these quasars are spatially unresolvable. Reverberation mapping is now beginning to unlock the physics of the broad emission line region (BELR) in nearby, low-luminosity quasars; however it is still unknown whether this gas is dominated by virial motion, by outflows or infall. The challenge is greater for more distant, powerful sources due to the very long response time of the BELR to changes in the continuum. We present a new technique for probing the kinematic properties of the BELR and accretion disc of high-z quasars using differential microlensing, and show how substantial information can be gained through a single observation of a strongly lensed quasar using integral field spectroscopy. We apply this technique to integral field spectroscopy of the multiply imaged quasar Q2237+0305, and find that the observed microlensing signature in the C iii] broad emission line favours gravitationally dominated dynamics over an accelerating outflow.